Overtime and psychological well-being among Chinese office workers - Houdmont, Jonathan; Zhou, Jieming; Hassard, Juliet (Oxford Journals, 2011)
Background: Research on the relationship between overtime and psychological well-being, and workers’ perceptions of the factors that determine overtime, has been conducted exclusively in the Western cultural context. Aims: To examine whether existing theory and evidence can be applied to a non-Western cultural setting by investigating the constructs among a sample of office workers drawn from a Chinese branch of an international information and communication technology company. Methods: Data were collected from 130 full-time employees on overtime hours worked, psychological well-being, and four variables identified by participants as being important determinants of overtime: job demands, intrinsic motivation, anticipated rewards, and overtime work culture. T-tests and multiple linear regression analyses were used to examine the relationship between variables. Results: All study participants had worked overtime in the previous 6 months period; the mean weekly overtime rate was 14.2 h. High overtime employees demonstrated significantly lower levels of psychological well-being than those who worked low levels of overtime. In combination, the four reasons for working overtime predicted approximately one-fifth of the variance in overtime hours worked, suggesting that knowledge of these variables could be used by practitioners to predict the amount of overtime in which workers are likely to engage. Conclusions: The findings suggest that existing theory and evidence may apply beyond the individualist cultural context. The findings might usefully inform the organization of work in collectivist cultures and the implementation of multinational operations in these cultures.